Unveiling the potential of cellulose nanofibre based nitrogen fertilizer and its transformative effect on Vigna radiata (Mung Bean): nanofibre for sustainable agriculture - Sharma, Neha; Kochar, Mandira; Allardyce, Benjamin James; Rajkhowa, Rangam; Agrawal, Ruchi (Frontiers in Plant Science, 2024)
Fertilizer management is crucial to maintaining a balance between environmental health, plant health, and total crop yield. Farmers are overutilizing fertilizers with a mind set to enhance the productive capacity of the field, which adversely impacts soil fertility and causes serious environmental hazards. To mitigate the issues of over-utilization of fertilizers, controlled-release fertilizers were developed using nitrogen fertilizer (ammonium chloride) loaded on cellulose nanofibres (named CNF*N). In this study, the effects of CNF*N were compared with commercial nitrogen fertilizer (ammonium chloride) on Vigna radiata (Mung) under greenhouse conditions. The pot experiment was conducted using six treatments: first treatment was control, where the plant was cultivated (T1); second treatment was T2, where the plant was cultivated with CNF to determine the impact of CNF on the plant; third was T3 where commercial ammonium chloride (24 mg/ 2 kg soil) was added to the plant; fourth was T4, where the plant was loaded with CNF, viz. CNF*N contains 4.8 mg of nitrogen; fifth was T5 CNF*N pellet contains 12 mg of nitrogen, and the last sixth treatment (T6) where CNF*N pellet containing 24 mg of nitrogen.Results indicated that the growth parameters were best achieved in T6 treatment. Plant height was at its maximum in the T6 treatment (44.4 ±0.1cm) after the second harvest, whereas the minimum plant height was observed in T1, which was 39.1 ±0.1 cm. Root-to-shoot weight ratio was also maximum in T6 (0.183± 0.02) and minimum in T1 (0.07± 0.01) after second harvesting. The significant difference among the treatments was determined with Tukey's honestly significant difference (HSD). The nitrogen content (available and total) was significantly higher in the T4, T5, and T6 treatments (0.22, 0.25, and 0.28%) as compared to the control treatments (T1 (0.12%), T2 (0.13%), and T3 (0.14%) during the second harvesting stage (90 days), as nitrogen plays a crucial role in the development of vegetative growth in Vigna radiata. The rate of controlled-release nitrogen-fertilizer was found to be optimal in terms of plant growth and soil nutrients; hence, it could potentially play a crucial role in improving soil health and the yield of the crop.